An ethnopharmacological survey of medicinal plants used for wound care in the Fez-Meknes region (Morocco) - El Ghazal, Anouar; Louafi, Boutaina; Sebbar, Khaoula; El Mekkaoui, Anas; Ibnsouda Koraichi , Saad; El Abed , Soumya (Ethnobotany Research and Applications, 2025)
Background: Wound healing is a complex medical challenge shaped by diverse biological processes and wound types. In Morocco, medicinal and aromatic plants have been integral to traditional wound care for centuries. However, their use remains poorly documented. To bridge this gap, we conducted an ethnopharmacological study in the Fez-Meknes region, a botanically rich area where phytotherapy plays a crucial role in local healthcare. This study catalogs the plant species used for wound treatment, exploring their preparation methods, applications, and therapeutic significance. Methods: Over an eight-month period, semi-structured questionnaires were administered to 507 herbalists and traditional healers across seven provinces. Traditional knowledge was assessed using statistical indices such as the Relative Frequency of Citation (RFC), Family Importance Value (FIV), and Rahman’s Similarity Index (RSI). The information gathered included plant species used, their parts, states (fresh or dried), preparation methods, application modes, and their roles in treating different wound healing stages, based on the wound color scale (wound healing continuum). Statistical significance and correlation analyses were conducted to examine the relationships within the collected data. Results: A total of 46 plant species from 26 botanical families were identified. Lamiaceae (FIV= 0.048), Asteraceae (FIV= 0.047) and Asphodelaceae (FIV= 0.032), emerged as the most frequently cited families, with notable species such as Dittrichia viscosa (L.) Greuter (RFC= 0.199) and Teucrium polium (L.) (RFC= 0.134), known for their analgesic and wound healing properties. Leaves were the most commonly utilized plant part (PPV = 0.544). Fresh plant materials accounted for 74.16% of preparations, predominantly applied in raw or liquid form through wrapping or irrigation. Despite variations in floristic similarities across provinces and regions, the Fez-Meknes region stands out for its rich phytotherapeutic and cultural heritage. Conclusions: The Fez-Meknes region's ethnopharmacological richness makes it a prime source for innovative plant-based wound therapies. These traditional medicinal plants hold substantial promise for improving and optimizing wound care practices. Further pharmacological and phytochemical investigations are recommended to validate their therapeutic efficacy. Keywords: Ethnopharmacology, Fez-Meknes region, Medicinal plants, Phytotherapy, Traditional knowledge, Wound healing continuum, Wound treatment.